The Quality Bonding of Sembilang Bamboo (Dendrocalamus giganteus Munro) Using Isocyanate Adhesive - Ajeng Rahmawati; Ina Lidiawati; Meiganati, Kustin Bintani; Ignasia Maria Sulastiningsih (Sains Natural: Journal of Biology and Chemistry, 2025)
The increasing demand for wood-based products is not balanced by a sufficient timber supply, creating a need for alternative materials such as bamboo. Dendrocalamus giganteus Munro (bamboo sembilang) is a promising substitute; However, its inherent limitations require modification, particularly through lamination technology. Adhesion plays a crucial role in this process as it strongly affects surface wettability and bonding strength.One important factor in the conversion of bamboo into laminated boards is the adhesion process, as it significantly affects the wettability properties and bond strength. This study aimed to evaluate the wettability characteristics of bamboo sembilang and its bonding strength with isocyanate adhesive, considering the effects of surface orientation, adhesive spread rate, and pressing time. Wettability was assessed using the contact angle method and the Corrected Water Absorption Height (TAAT), while bonding strength was tested under dry and wet conditions. Results showed an average contact angle of 33,40° on the inner surface and 35,14° on the outer surface of bamboo, with a TAAT value of 103.51 mm, indicating good wettability. The average dry bonding strength was 68.4 kg/cm², meeting the JPIC (2007).  These findings demonstrate that bamboo sembilang has strong potential as a raw material for laminated boards with reliable bonding performance when using isocyanate adhesive.